Design and Implementation of Treasure Kids Smart (TKS) Game-Based Learning Media to Improve Students’ Numeracy Performance in Primary Education - Rifdah Luthfia Salmaa; Ahmad Fadilah Arif; Septy Nurfadhillah (International Journal of Management, Innovation, and Education, 2024)
This study aims to design and implement Treasure Kids Smart (TKS), a game-based learning media developed to enhance the numeracy performance of primary school students. The research was motivated by the need to improve arithmetic competence and learning engagement among fifth-grade learners at SDN Cikokol III, Tangerang, through interactive and technology-driven instruction. Using the Research and Development (R&D) approach adapted from the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study systematically developed the TKS media combining educational content, visual storytelling, and gamification principles to foster problem-solving and computational thinking. Data were collected through expert validation, pre-test and post-test assessments, and user feedback questionnaires to measure both the effectiveness and feasibility of the media. The results indicate that TKS effectively improved students’ numeracy skills, reflected in a significant increase in post-test scores compared to pre-test results (gain score = 0.47, moderate category), as well as high user satisfaction ratings from both teachers and students (average validity score = 92%). The findings suggest that integrating digital game-based learning into mathematics education promotes engagement, motivation, and conceptual understanding, making TKS a viable innovation for enhancing numeracy learning in Indonesian primary schools.